2020
DOI: 10.1039/c9cp05342e
|View full text |Cite
|
Sign up to set email alerts
|

Phase transition and mechanical properties of cesium bismuth silver halide double perovskites (Cs2AgBiX6, X = Cl, Br, I): a DFT approach

Abstract: Double perovskite-based silver and bismuth Cs2AgBiX6 (X = Cl, Br, I) have shown a bright future for the development of low-risk photovoltaic devices due to their high stability and non-toxicity of their elements, unlike Pb-based perovskites.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(13 citation statements)
references
References 28 publications
0
13
0
Order By: Relevance
“…Generally, cubic crystals with mechanical stability should meet the following conditions for C ij : C 11 – C 12 > 0, C 44 > 0, C 11 + 2 C 12 > 0, and C 12 < B < C 11 . For Cs 2 AgBiBr 6 , the calculated C i j values for Cs 2 AgBiBr 6 meet the above criteria, indicating excellent mechanical stability. In addition, the calculated Young’s modulus, shear modulus, and Poisson’s ratio values differ in different directions, indicating that the Cs 2 AgBiBr 6 in the cubic phase was elastically anisotropic as shown in Figure . The linear and volumetric thermal expansion coefficients for Cs 2 AgBiBr 6 are 27.8(3) and 83.9(10) M K –1 , receptively, which are lower than those of Pb-based halide perovskites due to the stronger bonding characteristics.…”
Section: Structural and Photoelectric Properties Of Cs2agbibr6mentioning
confidence: 86%
“…Generally, cubic crystals with mechanical stability should meet the following conditions for C ij : C 11 – C 12 > 0, C 44 > 0, C 11 + 2 C 12 > 0, and C 12 < B < C 11 . For Cs 2 AgBiBr 6 , the calculated C i j values for Cs 2 AgBiBr 6 meet the above criteria, indicating excellent mechanical stability. In addition, the calculated Young’s modulus, shear modulus, and Poisson’s ratio values differ in different directions, indicating that the Cs 2 AgBiBr 6 in the cubic phase was elastically anisotropic as shown in Figure . The linear and volumetric thermal expansion coefficients for Cs 2 AgBiBr 6 are 27.8(3) and 83.9(10) M K –1 , receptively, which are lower than those of Pb-based halide perovskites due to the stronger bonding characteristics.…”
Section: Structural and Photoelectric Properties Of Cs2agbibr6mentioning
confidence: 86%
“…A similar indirect bandgaps were observed for other Bi‐based perovskite materials, including Cs 2 AgBiBr 6 and Cs 3 Bi 2 I 9 . [ 4,5,48,49 ] The valence band maximum was closer to the Fermi energy level, demonstrating the properties of a P‐type semiconductor. The corresponding projected density of states (PDOS) was calculated to further evaluate the electronic structure of (BAH)BiI 4 (Figure 3b).…”
Section: Optoelectronic Propertiesmentioning
confidence: 87%
“…These results indicated that the thermodynamic stability of Cs 2 AgInBr 6 and Cs 2 AgInI 6 are poorer than that of chloride counterparts. In summary, the goldschmidt factor t , octahedral factor μ and decomposition enthalpies can be performed to assess their stability, [ 171,172 ] which give insights into the HDP stability and develop strategies for making more efficient LED devices.…”
Section: Stability Of Halide Double Perovskite Nanocrystalsmentioning
confidence: 99%